A novel shallow bore ground heat exchanger for ground source heat pump applications—Model development and validation. (5th January 2020) - Warner, Joseph; Liu, Xiaobing; Shi, Liang; Qu, Ming; Zhang, Mingkan
Highlights: A novel low-cost ground heat exchanger (GHE) was introduced. A one-dimensional (1D) model of the new GHE was developed and validated. The 1D model is computationally much more efficient than 3D model. New GHE has similar performance as and lower cost than conventional GHE. Abstract: A novel ground heat exchanger design, the Underground Thermal Battery (UTB), was proposed as a low-cost alternative to the conventional vertical bore ground heat exchanger (VBGHE) for the application of ground source heat pumps (GSHPs). The UTB is designed to be installed in a shallow borehole (less than 6 m deep) and thus could cost much less than the conventional VBGHE, which usually is installed in vertical bores 60 m deep. By utilizing natural convection of water and phase change materials, the UTB tempers its temperature change in response to thermal loads, which helps improve the efficiency of GSHPs. A one-dimensional (1D) model of the UTB has been developed and validated with the measured performance data of a small-scale UTB, as well as the simulation results of a more detailed three dimensional (3D) numerical model, which accounts for both heat transfer and fluid dynamics in the UTB. This 1D model is computationally much more efficient than the 3D model and thus can simulate the annual performance of the UTB with acceptable computation time. The 1D model has been used to evaluate the performance of the UTB so that it can be compared with the conventional VBGHE.